Hijacking Spoofing Attack and Defence Strategy Based on Secured Network Protocols - Aravind, B; Murugan, D (International Journal of Computer Sciences and Engineering, 2025)
Spoofing and Hijacking is a major threat in network security. Spoofing involves attacks that which are associated with the impersonation of third party to steal the credential information’s from a network. Major IP spoofing attacks includes ARP spoofing attacks and DNS spoofing attack, which targets the server. This attack is also called as IP address forging which tries to take away the major information’s from the organizations network systems. There are several tools available to prevent this intrusion prevention system. Some of them are snort, suricata, firewall, netfilter and IPfilter.Penetrating into the network can be prevented using be found using some testing tools like Nmap, Netcat and Hping. Certain attacks denial of service attack and man in the middle attack are more prone to these penetrating malicious threats. Therefore, it is mandatory to take necessary actions to prevent network from these attacks. Defensive strategies like filtering the packets, using an upper layer, using access control list and using a router that is encrypted in nature are encouraged to make the network secure. In this paper, various hijacking spoofing attack is analyzed and their preventive methods are mentioned to enable the network to be well secured. Certain specific protocols are encouraged to do this security measure to prevent the network attacks.